Perbedaan Keakuratan Pengukuran Proporsi Tinggi Wajah Menggunakan 3DF Zephyr Dibandingkan Metode Secara Langsung - Susantoputri Angenia Helza, Victoria; Gadih Pratomo, Harris (Fakultas Kedokteran Gigi Universitas Trisakti, 2025)
Background: Facial balance serves as an early indicator for dentists in analyzing patient's facial skeletal structure. It can be analyzed by comparing the height proportion of the upper (trichion-glabella), middle (glabella-subnasale), and lower (subnasale-menton) face regions. Ideal facial balance is achieved when the distance between facial parts is equal. Currently, facial height measurement can be done digitally using 3D models with photogrammetry, a cost-effective, efficient, and non-invasive technique for reconstructing and measuring 3D models. 3DF Zephyr can be an option for reconstructing and measuring 3D models. Objectives: This study aims to determine the differences in accuracy of measuring facial height proportion using 3DF Zephyr and the direct method. Methods: A total of 32 subjects of preclinical students from Faculty of Dentistry Universitas Trisakti, aged 19-21 years old were measured for facial height proportion on the upper, middle, and lower face regions using a caliper. Next, 50 facial photographs were taken from various directions, angles, and positions using smartphone camera, then reconstructed and measured as a 3D model using 3DF Zephyr. Results: The independent t-test showed no significant difference between the two methods (p>0,05). Conclusion: There is no significant difference between 3DF Zephyr and the direct measurement in measuring facial height proportion.